Bariery rozwoju pracy socjalnej w pomocy społecznej w perspektyivie systemowej. Przykład pracy socjalnej z rodziną - Trawkowska, Dobroniega (Wydawnictwo Naukowe UAM, 2010)
The article aims at answering the questions: what can and should be done, what does social work with the family, so entangled in numerous barriers, need? Social work, including social work with the family, requires good strategies. These can be in the form of organisational solutions that help to bridge rescue and prevention. These can also be a skilful combination of therapy and social and cultural activities; they can a planned form of support for other traditional methods in social work. They can refer to the enlargement of the system of professional support from professional helpers. They can create a generic framework for activities in the form of good local strategies and family support programmes.
Barriers in the development of social work in social service from a systemic perspective. The case of social work with the family